Appreciation of House Price and its Impact to Reverse Mortgage Pricing - Syahira Miskam, Ameira; Fadhil Erwin, Muhammad; Amira Abd Rahman, Nurul; Mohamed Redzwan, Norkhairunnisa (International Journal of Engineering and Technology, 2018)
Reverse mortgage is a loan against home equity providing cash advances to a borrower and requiring no repayment until the homeowner dies or permanently moves out of the house. The reverse mortgage is a financial instruments that help elderly to sustain their retirement years by liquidity of their equity assets. The amount of reverse mortgage that can be received depends on home’s appraised value, loan’s interest rate and borrower age at the time of application. This study aims to determine the appreciation of house price in Malaysia and its effect on the price of reverse mortgage. The results obtained are able to aid retirees to better manage their retirement income.